Seasonal variation in physical characteristics of native buck ( Capra hircus) semen in Andhra Pradesh - SRINIVAS, M; NAIDU, K VENUGOPAL; CHETTY, A VENKATAMUNI (The Indian Journal of Animal Reproduction, 2023)
Five native buks aged between 2 to 2a years and weighing about 24.25±2.5 kgs were used to study theseasonal variation in physical attributes of semen. Semen samples were collected twice in a week during winter andsummer seasons. The mean values for different semen characteristics were as follows, volume 0. 70±0.10 and0.60±0.02, mass motility 4.46±0.06 and 4.34±0.08, individual motility(%) 81 .78±0.53 and 78.06±0.68, spennconcentration (x I 09/ml) 2.45±0.31 and 2.35±0.02, live sperm count(%) 87.05±0.62 and 81.11±0.51, abnormal spenn(%) 8.98±0.23 and 9.28±0.20 and intactacrosomes(o/o) 72.68±0.97 and 77.76±0.76 in winter and summer seasonsrespectively. Seasons had significant effect on semen volume, individual motility, spenn concentration, live spenncount, abnonnal sperms and intact acrosomes acrosomes where as mass motility did not significantly differ betweenthe seasons.
Keywords: Serum; sperm concentration; live sperm; seasonal; buck